The Influence of First Child Supply Chain Policy for Human Recourse Management Based On Local Wisdom Ethnic SSCM in Indonesia - Rismawati, Rismawati; Hajar, Siti; Kismarsilah, Kismarsilah; Pageno, Isbon (International Journal of Supply Chain Management, 2020)
Abstract- This research aims to empirically determine the SSCM knowledge on Human management at in Indonesia. Suppliers of the materials and equipment to the laboratory where the first discovery is made are in many cases replaced by larger players with capabilities to provide a broader range of materials, services, and support. During this evolution there are many lessons to be learned, not the least of which is that it is imperative to take into account the nuances of supply chain management that can make the difference between success and failure. Informants were selected through purposive and snowball sampling. The results showed the Sustainable Supply Chain Management (SSCM) Ethnic believes the Human management strategy is one of the custom traditions to be observed by mothers in their first supply chain policy for human resource management to avoid bad things happening to the socie-economic